ANÁLISE MULTIESCALAR DOS DEPÓSITOS FLUVIAIS DA FORMAÇÃO JAICÓS, BACIA DO PARNAÍBA - Moreira, Anderson Camargo; Mantovani, Iara Frangiotti; Santos, Allan Ataide Ribeiro dos; Manna, Monica Oliveira; Bállico, Manoela Bettarel; Metzner, Mariah (Boletim Paranaense de Geociências, 2025)
Braided fluvial deposits, such as the Jaicós Formation, Serra Grande Group, Parnaíba Basin, represent important aquifers and reservoirs that possess distinct properties due to different lithologies. Multiscale analysis of these deposits is an important tool for estimating fluid behavior within the reservoir. This study proposes a multiscale analysis, correlating petrophysical and petrographic parameters with architectural elements of the Jaicós Formation, through the characterization of identified deposits from a Digital Outcrop Model (DOM), correlated with three-dimensional images obtained by X-ray computed microtomography and thin sections. The correlation of architectural elements – gravel bars, simple and compound downstream accretion element, and sand bedforms – revealed significant variations in porosity and permeability, influenced by depositional facies and diagenetic processes. While gravel and downstream accretion element exhibit fair to good porosity and excellent permeability, sand bedforms have insignificant porosity and low permeability due to the high cementation identified in the samples, causing this element to act as a flow barrier. Petrographic analysis showed that the rocks are predominantly quartz arenites with indications of diagenetic processes, including intense mechanical compaction, cementation by iron oxides-hydroxides, clay infiltration, and authigenic clay formation, resulting in a drastic reduction of primary porosity. Secondary porosity, generated by feldspar dissolution and quartz grain fracturing, occurs locally and is generally filled with clays. The results indicate that, although the Jaicós Formation presents intervals of good porosity and permeability, internal heterogeneity and diagenetic processes control reservoir compartmentalization.